Coins Operated Pizza Vending Machine - Mahfouz, Ahmad; Khalifa, Abed-Alrahem; Shahateet, Mohammad (جامعة بوليتكنك فلسطين - طاقة, 2019)
البيتزا هي من أسرع األطعمة التي يتم طلبها في األسواق وبسبب قلة عدد مطاعم البيتزا و معظم الناس ال يعرفون كيف يصنعها والطلب الكبير عليها من قبل الناس . لذلك ، قررنا تصميم وتنفيذ ماكينة أوتوماتيكية بأبعاد )3 م طوالً ، 1.5 م عرض( إلنتاج البيتزا بجودة عالية دون االنتظار في األسواق . يحتوي النموذج األولي الذي تم تصنيعه على ستة أجزاء رئيسية: كاشف العمالت ، ثالجة , توزيع الصلصة , توزيع خضروات ، توزيع جبنة وفرن. تم إجراء التجارب على النحو التالي ، يتم تفعيل كاشف العمالت بواسطة قطعة معدنية من صنف 5 شيكل ، ثم يتم أنزال قطعة العجينة من السير الناقل الذي بداخل الثالجة الى السير الناقل الرئيسي ، وبعدها يتم أضافة الصلصة ، الخضروات و الجبنة ، واخيرا يتم دخول قطعة البيتزا الى الفرن لمدة 10 دقائق وبعدها ينتج لنا قطعة بيتزا جاهزة لألكل ، بالفعل تم إنتاج بيتزا . مزايا أستخدام هذه الماكينة هي لتوفير الطاقة البشرية )األيدي العاملة ( والمال والوقت ، ويقع هذا الجهاز في األماكن العامة . Pizza is the fastest food ordered and Due to the small number of pizza restaurants and Most people don't know how make it and the high demand on it by people. So, we decided to design and implement an automatic machine with dimensions (3m long,1.5m width) , make to produce pizza with high quality without waiting in markets . The prototype contains a six main parts: Coins Detector, Refrigerator ,sauce distribution, Cheese distribution ,Vegetable distribution and Baking stage, with experiments as follows. is Activated the Coins Detector by pay 5 (₪), then the dough piece from the conveyor belt inside the refrigerator is download to the main conveyor belt , and adding the materials (sauce, vegetables and cheese) to the dough piece, , and finally the entry the piece pizza into the oven For 10 minutes . Already A Pizza has been produced. The advantages of using this machine are for save the man power, money and time, this machine is located in public places.
CD , no of pages 74, طاقة 9/2019
Keywords: Vending Machines